It. Chapter two [videorecording (DVD)] - Wolfhard, Finn, 2002-; Skarsgård, Bill; Chastain, Jessica, 1977- (Warner Home Video, 2019)
Twenty-seven years after they defeated Pennywise, he has returned to terrorize the town of Derry once more. When kids start disappearing again, Mike, the only one who stayed in Derry, calls the others to come home. Each damaged by the experiences of the past, they must conquer their fears to destroy Pennywise once and for all.